Preliminary Determination of Footprint Area of Uncontrolled Space Debris: Case Study of Tiangong-1 Space Station - Nizam Ahmad; Elisa Fitri (Indonesian Journal of Geography, 2021)
Indonesia is an archipelagic country consisting of 16,056 islands and covering a vast area around 5,120km x 1,760km. With the largest coastline in the world, Indonesia is vulnerable to the fall of human-made objects from space. Furthermore, the space objects placed at polar and equatorial regions pass over the equatorial region, including Indonesia, more frequently around 4 and 9 times a day, successively depending on their altitudes. Due to the significant probability of the passages, determining the footprint of falling space objects (debris) is mandatory. Therefore, this study examines the demise of Tiangong 1 as a case study. First, trajectory propagation was carried out to track the re-entry point resulting in an estimated footprint area of around 2,632 km x 2,698 km over the Sothern Pacific Ocean.  Second, a mathematical formulation in Astrodynamics was applied to engage a series of assumptions, which led to a more cramped footprint area of around 193km x 12km over a small portion of the South Pacific Ocean. Since the orbital prediction is fraught with great uncertainty, it was very likely that the Tiangong-1 debris fell over the Southern Pacific Ocean of the order of thousands of kilometers.